KINERJA KARYAWAN YAYASAN PENDIDIKAN KARTINI NUSANTARA DI PENGARUHI OLEH BUDAYA ORGANISASI MELALUI LINGKUNGAN KERJA SEBAGAI VARIABEL INTERVENING - Edy Sanusi Silitonga; Noni Triana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2024)
The research objective to be achieved is to determine the influence of organizational culture on employee performance at Yayasan Pendidikan Kartini Nusantara through work environment. This research uses quantitative methods. The population in this study were employees of Yayasan Pendidikan Kartini Nusantara. The technique used for sampling is a saturated sample, all members of the population are sampled. The data analysis method uses path analysis. The research results can be concluded as follows: 1) The organizational culture has a direct and significant effect on employee performance. 2) The work environment has a significant direct effect on employee performance. 3).The organizational culture has a significant direct effect on work environment. 4) The organizational culture does not have a positive and significant indirect effect on employee performance at Yayasan Pendidikan Kartini Nusantara through work environment